Шевченків лист до невідомої: проблема адресата - Боронь, О.В. (Слово і Час, 2019)
Автор статті, проаналізувавши аргументи публікаторів Шевченкового листа від 28 липня
1860 р., остаточно відкидає можливість його адресації Ликері Полусмак і пропонує кілька
уточнень у коментарі до цього та кількох інших, пов'язаних із ним листів. Неприйнятною
визнано також версію упорядників Повного зібрання творів Шевченка в десяти томах про те,
що лист призначався Анні Шариковій, адже поетове знайомство з нею так і не доведено. Автор
обґрунтував гіпотезу, що незавершена записка адресувалася Амалії Клоберг – продавчині
магазину малярського приладдя Фелікса Аванцо. За припущенням дослідника, вона могла бути
натурницею для кількох Шевченкових малюнків. The author of the article analyzed the arguments of other researchers and finally disproved the
version that Shevchenko’s “letter to unknown woman” could be addressed to Lykera Polusmak. He
also offers a few clarifications in the comments to this and several other related letters. The Russian
language is the main and indisputable argument against addressing the letter to Lykera, despite the
fact that, although badly, she could read in Russian and was even able to write a few words with great
difficulty. The author suggests publishing several Shevchenko’s household notes, contained on the
pages of Lykera’s notebook, in the new “Complete Works”.
The version of the researchers who compiled Shevchenko’s “Complete Works” in 10 volumes
that the letter was intended for Anna Sharikova has been recognized as inconsistent. The published
archival materials, previously unavailable to the general public, do not give ground to speak even
about Shevchenko’s acquaintance with A. Sharikova. Her petitions to various authorities are full of
fantastic allegations, none of which was confirmed. According to the documents, officials were inclined
to consider her insane.
Having offered Lykera to marry on July 27 1860, and having obtained her prior consent on the 28th
(subject to the absence of a denial from her former master M. Makarov), Shevchenko on the same day,
i.e. July 28, wrote a letter to a person associated with him, obviously being in intimate relationship,
which had to be completely broken off. The author substantiated the hypothesis that an unfinished
note was addressed to Amalia Kloberg, which was a seller at F. Avanzo’s art store in St. Petersburg.
He also supposes that A. Kloberg could be a model for several Shevchenko’s drawings. At the same
time, it is probable that the note was intended for the person still unknown to us, therefore the previous
decision of the researchers compiling academic editions of Shevchenko’s works remains valid: to print
the text as a letter to the unknown.